1985
DOI: 10.21273/jashs.110.6.846
|View full text |Cite
|
Sign up to set email alerts
|

Net CO2 Assimilation Rate and Nitrogen Content of Grape Leaves Subsequent to Fruit Harvest

Abstract: The relationship between net CO2 assimilation rate (A) and nitrogen (N) content during leaf senescence was determined on field grown Vitis vinifera L. ‘Thompson Seedless’ leaves. Measurements commenced subsequent to fruit harvest and were made at weekly intervals until leaf fall. Maximum A was greater than 2.0 nmoles CO2 cm-2s-1 when leaf N content was greater than 3.0%. There was a linear relationship between A and percent N content regardless of whether A was expressed on an area or dry weight basis. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Once the vines had filled up their pool of storage reserves, they simply began to shut down and initiated a premature senescence program in the leaves. Williams and Smith (1985) found that leaf nitrogen declined in concert with photosynthesis during postharvest leaf senescence in grapevines. We suggest that early leaf senescence brought about by low overall sink strength may be an adaptive strategy: vines may benefit from the ability to remobilize leaf nitrogen, as well as other nutrients, sooner for storage in the perennial structure.…”
Section: Discussionmentioning
confidence: 98%
“…Once the vines had filled up their pool of storage reserves, they simply began to shut down and initiated a premature senescence program in the leaves. Williams and Smith (1985) found that leaf nitrogen declined in concert with photosynthesis during postharvest leaf senescence in grapevines. We suggest that early leaf senescence brought about by low overall sink strength may be an adaptive strategy: vines may benefit from the ability to remobilize leaf nitrogen, as well as other nutrients, sooner for storage in the perennial structure.…”
Section: Discussionmentioning
confidence: 98%
“…Since 70% of the solar radiation absorbed by a grapevine canopy takes place in the first leaf layer (16), these leaves would be expected to have the highest N concentration among leaves within the canopy. Since there is a linear relationship between leaf N concentration and net C 0 2 assimilation of grape leaves (23), the partitioning of N as demonstrated in Table 1 would optimize canopy photosynthesis by increasing N in leaves that are directly responsible for the majority of the carbon assimilated by the grapevine.…”
Section: Discussionmentioning
confidence: 99%